2015
DOI: 10.3832/ifor1321-007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of four levels of shade on survival, morphology and chlorophyll fluorescence of Nothofagus alessandrii container-grown seedlings

Abstract: © iForest -Biogeosciences and Forestry IntroductionNothofagus alessandrii Espinosa (ruil) is a threatened and endemic tree of the Mediterranean zone of Chile (UICN 2001). At the beginning of the last century, ruil forests have been subjected to logging and burning to clear land for cultivation (Donoso & Landaeta 1983), leaving the remnant populations highly fragmented and surrounded by Pinus radiata D. Don plantations (Bustamante & Castor 1998). Current anthropogenic pressures on ruil forests led to consider s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
(34 reference statements)
2
3
0
Order By: Relevance
“…Results from the current study support these explanations: species with similar chlorophyll concentrations at the start of the study also had similar chlorophyll fluorescence and by the end of the study, plants grown under shade had higher concentrations of chlorophyll and lower chlorophyll fluorescence. The differences in chlorophyll concentration due to shade in the current study are consistent with those reported earlier (Santelices et al., 2015; Wang et al., 2017).…”
Section: Resultssupporting
confidence: 93%
“…Results from the current study support these explanations: species with similar chlorophyll concentrations at the start of the study also had similar chlorophyll fluorescence and by the end of the study, plants grown under shade had higher concentrations of chlorophyll and lower chlorophyll fluorescence. The differences in chlorophyll concentration due to shade in the current study are consistent with those reported earlier (Santelices et al., 2015; Wang et al., 2017).…”
Section: Resultssupporting
confidence: 93%
“…This suggests that the optimal recruitment in N. alessandrii could be reached in forest gaps with intermediate levels of shade and moderate environmental stress (drought and light intensity). This is consistent with the results of Santelices et al (2015), who found that N. alessandrii seedlings performed better under intermediate shade (41-50% PAR) than under full sunlight conditions (100% PAR). In a recent study, Loewe et al (2017) experimentally evaluated the effects of shading and soil fertilization on the survival and stem length of N. alessandrii seedlings after one and two growing seasons under field conditions.…”
Section: Discussionsupporting
confidence: 92%
“…That is interesting since this species is considered as an early successional species in Brazil (Carvalho, 2004). Seedlings exposed to shaded conditions would allocate more biomass to stems and leaves, increasing their shoot/root ratio (Santelices et al, 2015). Higher mean of Mimosa bimucronata root biomass in larger containers resulted in more leaves only under shading, suggesting full sunlight inhibits biomass allocation to the shoot parts.…”
Section: Discussionmentioning
confidence: 99%